Design Space Exploration of Memory Model for Heterogeneous Computing - Lim, Jieun; Kim, Hyesoon (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2014: Anais do XXVI International Symposium on Computer Architecture and High Performance Computing, 2014)
Heterogeneous computing that combines a traditional CPU architecture with an accelerator has become a popular architecture. Memory modelling design decisions affect not only architecture designs but also programming models. Hence, comparing them is very challenging and not all design spaces have been explored. Although a unified memory address space that is fully coherent and strongly consistent across the entire memory system would be the ideal case, because of scalability and complexity, less ideal designs have been proposed. In this paper, we explore various design options quantitatively and qualitatively. Our results suggest that maintaining a separate memory model for each architecture and having a partially shared memory space provide the most design options in both programming models and architecture designs.